2009
DOI: 10.1007/s11095-009-9892-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-administration of Tacrolimus on the Pharmacokinetics of Multiple Subcutaneous Administered Interferon-Alpha in Rats

Abstract: Intravenous co-administration of tacrolimus (0.001 mg/kg) may be a promising way to assess crossover pharmacokinetic study of human or humanized proteinic formulations with multiple dosing schedules in an experimental animal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…3), whereas 0.001 mg/kg was effective in rats in our previous study. 8) Eiras et al 11) reported that tacrolimus shows similar immunosuppressive effects in rat and dog lymphocytes. It is well known that tacrolimus is mainly metabolized by the cytochrome P450 subfamily in the liver.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…3), whereas 0.001 mg/kg was effective in rats in our previous study. 8) Eiras et al 11) reported that tacrolimus shows similar immunosuppressive effects in rat and dog lymphocytes. It is well known that tacrolimus is mainly metabolized by the cytochrome P450 subfamily in the liver.…”
Section: Discussionmentioning
confidence: 96%
“…We recently reported that co-administration of the immunosuppressant tacrolimus suppressed specific antibody production following multiple administrations of protein-based drug h-IFN in rats. 8) In general, large animal species such as dogs or monkeys, which are close to humans, are used to evaluate the PK profiles of novel drug formulations. In the present study, we therefore extended our previous study to a larger experimen- tal animal, i.e., beagle dogs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations